Analisis Kebiasaan Konsumen Menggunakan Asosition Rule Metode Apriori Pada Central Retail X - Heru Mujianto, Ahmad; Faizah, Arbiati; Mashuri, Chamdan (Inovate, 2019)
The sustainability of a company will not be separated from the role of consumers in conductingtransactions. In fact, a consumer has different behaviour and character, therefore as a company owner mustbe able to analysis the patterns or habits of consumers in making transactions. This also happens in theretail center X, which has problems in the sales process, such as products running out of stock and unsoldproducts and the most popular products and products that are not in demand by consumers. Therefore weneed an analysis of consumer habits in conducting transactions. The method of association rule with apriori algorithm is able to be applied well in the analysis of the habits of consumer transactions in thecentral retail X. The results of the calculation obtained an average percentage of the value of support 33%40% and the value of confidence 43%-80%. The results of applying the association rule method with apriori algorithm can help recommend central retail X owners in structuring product and determine strategicsteps in increasing sales, such as providing discounts or promos for certain products.Keywords: Analysis, Consumer, Association Rule, Apriori, Retail.